HR MANAGEMENT AND WAR: IMPACT AND CONSEQUENCES FOR INTERNATIONAL CONSULTING COMPANIES IN UKRAINE - А. Р. Качур; Ю. П. Тадеєв; М. В. Шкробот (Ekonomìčnij Vìsnik Nacìonalʹnogo Tehnìčnogo Unìversitetu Ukraïni "Kiïvsʹkij Polìtehnìčnij Institut", 2024)
This study examines how military actions affect human resource management in the "Big Four" international consulting firms (Deloitte, PricewaterhouseCoopers, Ernst&Young, KPMG) in Ukraine. Wartime poses unique challenges like staff safety, business disruption, and the need for psychological support. These firms adapted by implementing flexible work arrangements, improving internal communication, and prioritizing corporate social responsibility. Consequently, they saw positive shifts in employer rankings, enhancing competitiveness in Ukraine's consulting market. However, issues such as motivation, talent retention, and fair reward systems warrant further HR management analysis and strategy development. The study offers insights into effective personnel management amidst instability.